2009
DOI: 10.1186/1471-2334-9-207
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the tuberculin skin test and interferon-γ release assay for detection of tuberculosis infection in immunocompromised patients in a BCG-vaccinated population

Abstract: BackgroundInterferon-γ release assay (IGRA) may improve diagnostic accuracy for latent tuberculosis infection (LTBI). This study compared the performance of the tuberculin skin test (TST) with that of IGRA for the diagnosis of LTBI in immunocompromised patients in an intermediate TB burden country where BCG vaccination is mandatory.MethodsWe conducted a retrospective observational study of patients given the TST and an IGRA, the QuantiFERON-TB Gold In-Tube (QFT-IT), at Severance Hospital, a tertiary hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 22 publications
(28 reference statements)
4
74
0
2
Order By: Relevance
“…In that study, highly advanced age, immunosuppressive treatment, lymphocytopenia (including CD4 ϩ lymphocytopenia), and hypoproteinemia could (12). In our study, based on the multivariate logistic regression analysis, taking immunosuppressive drugs, previously existing underlying diseases, bedridden status, and hypoalbuminemia were associated with increases in the frequency of indeterminate QFT-G IT test results.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In that study, highly advanced age, immunosuppressive treatment, lymphocytopenia (including CD4 ϩ lymphocytopenia), and hypoproteinemia could (12). In our study, based on the multivariate logistic regression analysis, taking immunosuppressive drugs, previously existing underlying diseases, bedridden status, and hypoalbuminemia were associated with increases in the frequency of indeterminate QFT-G IT test results.…”
Section: Discussionmentioning
confidence: 72%
“…Rates of indeterminate results of 5% to 40% for all participants and approximately 6% for health care workers have been reported (8-10). Rates of indeterminate results of 15.6% and 16.1% have been reported for two large tertiary care hospitals in South Korea (11,12). Considering the composition of the high-risk populations and the therapeutic approaches used at the hospital, the frequency of indeterminate results may vary depending on hospital conditions.…”
mentioning
confidence: 99%
“…This is evidenced in several studies looking at indeterminate tests as a function of lymphocytes. Kim et al found lymphocytopenia to be independently associated with indeterminate results (25). Similarly, a study looking at IGRA in patients with HIV found indeterminate results to correlate with CD4 counts ,200 cells/ml (22), further suggesting a strong correlation with depressed cell mediated immunity.…”
Section: Discussionmentioning
confidence: 96%
“…There are various conditions such as oncologic disease, HIV infection, anti-TNF-, corticoid or other immunomodulatory therapy, diabetes mellitus, renal failure or other immunocompromising conditions that are responsible for intermediate or false negative results (Schoepfer et al, 2008;Matulis et al, 2008;Kim et al, 2009). Particularly, the anti-TNF- treatment has increased recently, which hampers the activation of the innate immune responses, T cell mediated adaptive immune response and production of protective IFN-.…”
Section: Conditions Altering Igra Resultsmentioning
confidence: 99%